Kesalahan Penulisan Huruf Katakana シ (shi) Dan ツ (tsu) Pada Mahasiswa Semester 3 Pendidikan Bahasa Jepang FKIP UHAMKA: Writing Errors in Katakana Letters シ (shi) and ツ (tsu) in 3rd Semester Students of Japanese Language Education, FKIP UHAMKA - Apriliani, Mutiara; Anaresa, Futri; Hidayati, Deasy Wahyu (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
In the curriculum of the Japanese Language Education Study Program at Muhammadiyah  University, Prof. Dr. Hamka Jakarta, mastery of katakana letters is the main focus. However,  many students experience errors when writing katakana, which is believed to be caused by  short learning and the lack of use of katakana in textbooks. This research aims to describe  mistakes in writing Katakana letters by Class of 2022 students, with test results showing that  students tend to make mistakes, especially in stroke order or the order of strokes and writing.